Does Child Care quality matter? Associations between social-Emotional development and Non-parental Child Care in a representative Sample of Australian Children - Harrison, L (My University, 2008)
Drawing upon data from Wave 2 of Growing Up In Australia: The Longitudinal Study of Australian Children (LSAC), this article investigates the relationship between hours spent in early child care, the quality of that care, and children's social and behavioural development. International studies have reported that early and extensive use of child care can produce adverse socio-emotional effects, but they have also noted the ameliorating effects and positive benefits of high quality programs. This article tests these findings, comparing social and behaviour problems for children in formal care, in informal care, in mixed formal and informal care, and not attending care child, for children in the LSAC study aged 2 to 3 years, as reported by parents and carers. The results for social competence and behaviour problems for each group are discussed, and comparisons made with the international child care systems and studies. Overall, the research found that child care had a positive rather than a negative effect on children's social and emotional wellbeing.
Keywords: Child Care; Child Development; Child Development -- Emotional; Childhood and child development; Child Care; Child Development; Emotional; Childhood and child development